Pemanfaatan Silika Gel Hasil Pengolahan Abu Tongkol Jagung Termodifikasi TiO2 untuk Mengurangi Kadar Nitrat dalam Limbah Cair Tahu - Lulan, Theodore Y. K.; Ndolu, Intan C. M.; Nitti, Fidelis (Universitas Nusa Cendana, 2023)
Research has been conducted with the title Utilization of Silica Gel from the processing of TiO2-Modified Corn Cob Ash to Reduce Nitrate Levels in Tofu Liquid Waste. This study aims to determine the characteristics of silica gel from the processing of TiO2-modified corn cob ash in terms of functional groups and crystallinity and to determine the effectiveness of TiO2-modified silica gel to reduce nitrate levels in tofu liquid waste using pH, time and concentration parameters. The synthesis of silica gel from corn cob ash was carried out using the sol gel method. The results of FTIR characterization showed the successful synthesis of silica gel and TiO2 modified silica gel indicated by the presence of Si-O-Si and Si-OH absorption in silica gel and Ti-O-Ti absorption in TiO2 modified silica gel. The XRD data shows that silica gel has an amorphous structure and modified silica gel has an anatase structure. The results showed that the largest nitrate reduction occurred at pH 5 by 98.69%, contact time of 60 minutes by 97.39% and optimum concentration of 200 ppm by 98.94% with the largest silica adsorption capacity of 245.94 mg/g and the percentage of nitrate reduction in tofu liquid waste by 99.94%.